Vocabulary Learning Through Extensive Reading: A Case Study - Senoo, Yasuko; Yonemoto, Kazuhiro (Canadian Journal of Applied Linguistics, 2014)
Abstract The role and importance of reading in second language vocabulary learning have been discussed by many researchers because of the richness and variety of vocabulary in written texts compared to oral discourse (Horst, 2005; Nation, 2001). However, despite the recent increase of studies in this field, there are very few studies focusing on non-Western languages, including Japanese, compared to Indo-European languages. To fill the gap, this study explored the process of Japanese vocabulary acquisition through extensive reading. Data were collected through a pretest, eight immediate tests, a posttest, and a semistructured interview. The results indicate that extensive reading is especially beneficial in consolidating learners’ vocabulary knowledge and in encouraging learners to reflect on their interests and needs in vocabulary learning. Résumé Le rôle et l’importance de la lecture dans l’apprentissage du vocabulaire en langue seconde sont sujets de discussion pour de nombreux chercheurs en raison de la richesse et de la variété de la langue écrite en comparaison au discours oral (Horst, 2005 ; Nation, 2001). Toutefois, malgré la récente hausse d’études effectuées dans ce domaine, très peu d’études se concentrent sur les langues non-occidentales, incluant le japonais, en comparaison aux langues indo-européennes. Pour combler cette lacune, cette étude a exploré le processus d’acquisition du vocabulaire en japonais par la lecture assidue. Les données ont été recueillies grâce à un pré-test, huit tests immédiats, un post-test et une entrevue semi-structurée. Les résultats indiquent que la lecture assidue est particulièrement bénéfique pour la consolidation du vocabulaire des apprenants et pour encourager les apprenants à réfléchir à leurs intérêts et à leurs besoins dans l’apprentissage du vocabulaire.